The shadows of Ghadames - Stolz, Joelle (Yearling, 2004)
At the end of the nineteenth century in Libya, eleven-year-old Malika simultaneously enjoys and feels constricted by the narrow world of women, but an injured stranger enters her home and disrupts the traditional order of things.